APLIKASI WIDGET BERBASIS JAVA - Achmad Fikri Sallaby; Feri Hari Utami; Yode Arliando (Jurnal Media Infotama, 2015)
With the desktop widgets and Internet technologies are more advanced, it can be used to obtain information regarding the weather that has been going on and to know the temperature and the temperature of a region. Useful for more accurate delivery of information to the public for the purposes of the weather. According Garling and Bieber (2010) Widgets means software that consists of portable code that can be used on one or more platforms. Interface widgets are lightweight and relatively easy to use. In designing the application widget weather widget application authors raised, where the application of these widgets can provide weather information on an area. Where widget applications connected with the data connection on mobile phones that can connect to the internet. Java-based widget applications to facilitate and help people obtain information about the weather that has been going on and to know the temperature and the temperature of an area in real time. It is expected that these applications can be developed in other cases so as to increase knowledge on java programming and applications can be a reference weather circumstances connected with an internet connectionKeyword: Desktop Widget